Composition containing titanium dioxide nanotubes and application of composition in preparation of products for promoting differentiation of mesenchymal stem cells
By doping zirconium on the surface of titanium dioxide nanotubes and compounding with alginate gel, the problem of poor interface adhesion between nanotubes and titanium substrates is solved, the stability and biobinding ability of the nanotubes are improved, and the osteogenic performance is improved , and the mechanical strength and biocompatibility of the nanotubes are improved by heat treatment and the use of alginate gels.
Patent Information
- Application Number
- CN202411110306.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-13
AI Technical Summary
The interface adhesion between the titanium dioxide nanotube and the titanium substrate is poor, resulting in the nanotube being easily peeled off or broken, affecting the stability and biobinding ability of the composition, and its long-term stability in the biological environment is poor.
Interface adhesion is increased by doping zirconium on the surface of the titanium dioxide nanotube and recombining it with the alginate gel, and filling the alginate gel in an oxygen atmosphere by heat treatment to enhance the mechanical strength and biological activity of the nanotubes.
Improve the interface adhesion between the titanium dioxide nanotube layer and the titanium matrix, enhance the stability and biobinding ability of the composition, improve the osteogenic performance, and improve the nanotube through the use of zirconium doping and alginate gel mechanical strength and biocompatibility.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium dioxide nanotubes, in particular to a composition containing titanium dioxide nanotubes and its application in biomedicine. Background Art
[0002] Titanium dioxide nanotubes are one-dimensional nanostructured materials. They can be used as effective drug carriers because of their good biocompatibility and controllable pore size, making them potentially useful in biomedical fields such as drug delivery systems, tissue engineering, and biosensors. They can load various types of drug molecules, including chemotherapeutic drugs, antibiotics, anti-inflammatory drugs, etc. Titanium dioxide nanotubes can also promote cell adhesion and proliferation, so they are used in bone repair and regenerative medicine, or as sensitive elements for the construction of biosensors for the detection of biomarkers and other analytes.
[0003] Preparing a titanium dioxide nanotube structure on the surface of a titanium or titanium alloy substrate can simultaneously improve the bone integration and antibacterial properties of the substrate. However, the interfacial adhesion between the titanium dioxide nanotube layer and the titanium substrate is poor, which causes the titanium dioxide nanotube to be easily peeled off from the substrate or broken from the middle of the nanotube after being subjected to mechanical external force, affecting the stability and biocombination ability of the composition.
[0004] Although titanium dioxide nanotubes are generally considered biocompatible, long-term exposure or high-dose use may cause cytotoxicity, and their poor long-term stability in biological environments remains an urgent problem to be solved.
[0005] Therefore, it is necessary to design a composition containing titanium dioxide nanotubes and use the composition in preparing a product that promotes the differentiation of mesenchymal stem cells. Summary of the invention
[0006] The purpose of the present invention is to provide a composition containing titanium dioxide nanotubes and application thereof in preparing a product for promoting differentiation of mesenchymal stem cells.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: A composition containing titanium dioxide nanotubes, wherein the preparation method of the composition comprises the following steps: In the first step, the substrate is used as a working electrode and anodized in a fluorine-containing electrolytic solution to obtain an amorphous titanium dioxide layer on the substrate surface, and the surface-formed layer is removed by ultrasound; and a second anodization is performed under the same anodization conditions to obtain anodized amorphous titanium oxide nanotubes; The second step is to transfer the pure titanium and the surface amorphous titanium oxide nanotube material obtained in the first step to a zirconium-containing electrolyte for final anodization, wherein the zirconium-containing electrolyte comprises 0.5-1%wt ammonium fluoride and 0.1-0.6%wt zirconium ions, so as to obtain zirconium-doped titanium dioxide nanotubes grown on the surface of the substrate; The third step is to coat the alginate gel on the surface of the zirconium-doped titanium dioxide nanotubes obtained in the second step, and then evacuate the solution to completely remove the air in all the gaps so that the pores are filled with alginate gel, and then vacuum dry the solution; finally, the alginate gel material is compounded and filled in the amorphous titanium dioxide nanotubes on the surface of the substrate; In the fourth step, the product obtained in the third step is subjected to heat treatment to obtain a composition containing titanium dioxide nanotubes.
[0008] The substrate is titanium metal or titanium alloy.
[0009] In the first step, the fluorine-containing electrolytic solution includes 2-10 parts of ammonium chloride, 56-60 parts of propylene glycol, and 1-5 parts of potassium permanganate, calculated by mass.
[0010] In the first step, the voltage of the first anodization is 20-30V, and the time of anodization is 5-15 minutes.
[0011] In the first step, the voltage of the secondary anodization is 20-30V, and the anodization time is 5-15min.
[0012] In the second step, the voltage of the final anodization is 40-50V, and the anodization time is 20-30min.
[0013] In the third step, the preparation method of the alginate gel is as follows: sodium alginate powder is slowly added to deionized water while stirring until it is completely dissolved to obtain a solution with a concentration of 2%wt, dilute sodium hydroxide is used to adjust the pH value of the sodium alginate solution to 9 to promote the cross-linking reaction, and calcium ion solution is added dropwise to the sodium alginate solution, and the calcium ions immediately combine with the anionic groups on the alginate chain to form an alginate gel.
[0014] The heat treatment is carried out in an oxygen-containing atmosphere, the heat treatment temperature is 300-500° C., and the heat treatment time is 1.5-3 hours.
[0015] The pore diameter of the titanium dioxide nanotubes in the composition containing titanium dioxide nanotubes is 10-60 nm.
[0016] The composition containing titanium dioxide nanotubes is used for preparing a product for promoting the differentiation of mesenchymal stem cells.
[0017] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention composites cross-linked alginate on the surface of zirconium-doped titanium dioxide nanotubes to increase the interfacial adhesion between the titanium dioxide nanotube layer and the titanium metal or titanium alloy matrix, thereby improving the stability and biocombination ability of the composition.
[0018] 2. The present application dopes zirconium into titanium dioxide nanotubes, which can give play to the mechanical advantages of zirconium metal, while improving the biological activity of titanium materials and promoting the osteogenic properties of nanotube materials, thus solving the problems of insufficient strength and poor osteogenic properties of existing titanium dioxide nanotubes, and can be applied to the surface of implants to promote osteogenesis.
[0019] 3. Alginate is a natural polysaccharide extracted from brown algae, which has good biocompatibility and degradability. Alginate gel is used as a cross-linking material, which has excellent biocompatibility and low cost, and can improve the performance of the composition. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1 A composition containing titanium dioxide nanotubes, wherein the preparation method of the composition comprises the following steps: In the first step, the substrate is used as a working electrode and anodized in a fluorine-containing electrolytic solution to obtain an amorphous titanium dioxide layer on the substrate surface, and the surface-formed layer is removed by ultrasound; and a second anodization is performed under the same anodization conditions to obtain anodized amorphous titanium oxide nanotubes; The second step is to transfer the pure titanium and the surface amorphous titanium oxide nanotube material obtained in the first step to a zirconium-containing electrolyte for final anodization, wherein the zirconium-containing electrolyte comprises 1%wt ammonium fluoride and 0.3%wt zirconium ions, to obtain zirconium-doped titanium dioxide nanotubes grown on the surface of the substrate; The third step is to coat the alginate gel on the surface of the zirconium-doped titanium dioxide nanotubes obtained in the second step, and then evacuate the solution to completely remove the air in all the gaps so that the pores are filled with alginate gel, and then vacuum dry the solution; finally, the alginate gel material is compounded and filled in the amorphous titanium dioxide nanotubes on the surface of the substrate; In the fourth step, the product obtained in the third step is subjected to heat treatment to obtain a composition containing titanium dioxide nanotubes.
[0022] The substrate is titanium metal or titanium alloy.
[0023] In the first step, the fluorine-containing electrolytic solution includes 2 parts of ammonium chloride, 60 parts of propylene glycol, and 3 parts of potassium permanganate, calculated by mass.
[0024] In the first step, the voltage of the first anodization is 20 V, and the anodization time is 15 min.
[0025] In the first step, the voltage of the secondary anodization is 20 V, and the anodization time is 5 min.
[0026] In the second step, the voltage of the final anodization is 40 V, and the anodization time is 25 min.
[0027] In the third step, the preparation method of the alginate gel is as follows: sodium alginate powder is slowly added to deionized water while stirring until it is completely dissolved to obtain a solution with a concentration of 2%wt, dilute sodium hydroxide is used to adjust the pH value of the sodium alginate solution to 9 to promote the cross-linking reaction, and calcium ion solution is added dropwise to the sodium alginate solution, and the calcium ions immediately combine with the anionic groups on the alginate chain to form an alginate gel.
[0028] The heat treatment is carried out in an oxygen-containing atmosphere at a temperature of 300° C. for a time of 3 hours.
[0029] The pore diameter of the titanium dioxide nanotubes in the composition containing titanium dioxide nanotubes is 20 nm.
[0030] The composition containing titanium dioxide nanotubes is used for preparing a product for promoting the differentiation of mesenchymal stem cells.
[0031] Example 2 A composition containing titanium dioxide nanotubes, wherein the preparation method of the composition comprises the following steps: In the first step, the substrate is used as a working electrode and anodized in a fluorine-containing electrolytic solution to obtain an amorphous titanium dioxide layer on the substrate surface, and the surface-formed layer is removed by ultrasound; and a second anodization is performed under the same anodization conditions to obtain anodized amorphous titanium oxide nanotubes; The second step is to transfer the pure titanium and the surface amorphous titanium oxide nanotube material obtained in the first step to a zirconium-containing electrolyte for final anodization, wherein the zirconium-containing electrolyte comprises 0.5%wt ammonium fluoride and 0.6%wt zirconium ions, so as to obtain zirconium-doped titanium dioxide nanotubes grown on the surface of the substrate; The third step is to coat the alginate gel on the surface of the zirconium-doped titanium dioxide nanotubes obtained in the second step, and then evacuate the solution to completely remove the air in all the gaps so that the pores are filled with alginate gel, and then vacuum dry the solution; finally, the alginate gel material is compounded and filled in the amorphous titanium dioxide nanotubes on the surface of the substrate; In the fourth step, the product obtained in the third step is subjected to heat treatment to obtain a composition containing titanium dioxide nanotubes.
[0032] The substrate is titanium metal or titanium alloy.
[0033] In the first step, the fluorine-containing electrolytic solution includes 6 parts of ammonium chloride, 56 parts of propylene glycol, and 5 parts of potassium permanganate, calculated by mass.
[0034] In the first step, the voltage of the first anodization is 25 V, and the anodization time is 5 minutes.
[0035] In the first step, the voltage of the secondary anodization is 25 V, and the anodization time is 10 min.
[0036] In the second step, the voltage of the final anodization is 45 V, and the anodization time is 30 min.
[0037] The heat treatment is carried out in an oxygen-containing atmosphere at a temperature of 400° C. for a time of 1.5 h.
[0038] The pore diameter of the titanium dioxide nanotubes in the composition containing titanium dioxide nanotubes is 35 nm.
[0039] Example 3 A composition containing titanium dioxide nanotubes, wherein the preparation method of the composition comprises the following steps: In the first step, the substrate is used as a working electrode and anodized in a fluorine-containing electrolytic solution to obtain an amorphous titanium dioxide layer on the substrate surface, and the surface-formed layer is removed by ultrasound; and a second anodization is performed under the same anodization conditions to obtain anodized amorphous titanium oxide nanotubes; The second step is to transfer the pure titanium and the surface amorphous titanium oxide nanotube material obtained in the first step to a zirconium-containing electrolyte for final anodization, wherein the zirconium-containing electrolyte comprises 0.8%wt ammonium fluoride and 0.1%wt zirconium ions, so as to obtain zirconium-doped titanium dioxide nanotubes grown on the surface of the substrate; The third step is to coat the alginate gel on the surface of the zirconium-doped titanium dioxide nanotubes obtained in the second step, and then evacuate the solution to completely remove the air in all the gaps so that the pores are filled with alginate gel, and then vacuum dry the solution; finally, the alginate gel material is compounded and filled in the amorphous titanium dioxide nanotubes on the surface of the substrate; In the fourth step, the product obtained in the third step is subjected to heat treatment to obtain a composition containing titanium dioxide nanotubes.
[0040] The substrate is titanium metal or titanium alloy.
[0041] In the first step, the fluorine-containing electrolytic solution includes 10 parts of ammonium chloride, 58 parts of propylene glycol, and 1 part of potassium permanganate, calculated by mass.
[0042] In the first step, the voltage of the first anodization is 30 V, and the anodization time is 10 min.
[0043] In the first step, the voltage of the secondary anodization is 30 V, and the anodization time is 15 min.
[0044] In the second step, the voltage of the final anodization is 50 V, and the anodization time is 20 min.
[0045] The heat treatment is carried out in an oxygen-containing atmosphere at a temperature of 500° C. for a time of 2 hours.
[0046] The pore diameter of the titanium dioxide nanotubes in the composition containing titanium dioxide nanotubes is 50 nm.
[0047] Comparative Example 1 The difference between this comparative example and Example 1 is: In the second step, the concentration of zirconium ions in the zirconium-containing electrolyte is 0.02%wt.
[0048] Comparative Example 2 The difference between this comparative example and Example 1 is: In the second step, the concentration of zirconium ions in the zirconium-containing electrolyte is 0, and the concentration of sodium ions is 0.3%wt.
[0049] Comparative Example 3 The difference between this comparative example and Example 1 is: In the third step, agar is coated on the surface of the zirconium-doped titanium dioxide nanotubes obtained in the second step.
[0050] Comparative Example 4 The difference between this comparative example and Example 1 is: In the first step, the voltage of the first anodization is 10 V, and the anodization time is 15 min.
[0051] The voltage of the secondary anodization is 10V, and the time of the anodization is 5 minutes.
[0052] In the second step, the voltage of the final anodization is 20 V, and the anodization time is 25 min.
[0053] Comparative Example 5 The difference between this comparative example and Example 1 is: In the first step, the voltage of the first anodization is 40 V, and the anodization time is 15 min.
[0054] The voltage of the secondary anodization is 40V, and the time of the anodization is 5 minutes.
[0055] In the second step, the voltage of the final anodization is 60 V, and the anodization time is 25 min.
[0056] The mechanical strength of the compositions containing titanium dioxide nanotubes prepared in Examples 1-3 and Comparative Examples 1-5 was tested by a nanoindentation tester.
[0057] Table 1 Mechanical strength test results
[0058] As can be seen from Table 1, in Comparative Example 3, the alginate gel is not coated on the surface of the zirconium-doped titanium dioxide nanotubes obtained in the second step, resulting in a significant decrease in the structural stability and mechanical properties thereof.
[0059] Table 2 is a graph showing the results of the ALP activity of different compositions on bone marrow mesenchymal stem cells. As shown in Table 2, zirconium-doped titanium dioxide nanotubes have better osteogenic properties than undoped titanium dioxide nanotubes.
[0060] Table 2 ALP activity results
[0061] The above experimental results further prove the importance of the technical solution defined in the present invention to its technical effect.
[0062] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composition containing titanium dioxide nanotubes, characterized in that: The preparation method of the composition comprises the following steps: In the first step, the substrate is used as a working electrode and anodized in a fluorine-containing electrolytic solution to obtain an amorphous titanium dioxide layer on the substrate surface, and the surface-formed layer is removed by ultrasound; and a second anodization is performed under the same anodization conditions to obtain anodized amorphous titanium oxide nanotubes; The second step is to transfer the pure titanium and the surface amorphous titanium oxide nanotube material obtained in the first step to a zirconium-containing electrolyte for final anodization, wherein the zirconium-containing electrolyte comprises 0.5-1%wt ammonium fluoride and 0.1-0.6%wt zirconium ions, so as to obtain zirconium-doped titanium dioxide nanotubes grown on the surface of the substrate; The third step is to coat the alginate gel on the surface of the zirconium-doped titanium dioxide nanotubes obtained in the second step, and then evacuate the solution to completely remove the air in all the gaps so that the pores are filled with alginate gel, and then vacuum dry the solution; finally, the alginate gel material is compounded and filled in the amorphous titanium dioxide nanotubes on the surface of the substrate; In the fourth step, the product obtained in the third step is subjected to heat treatment to obtain a composition containing titanium dioxide nanotubes.
2. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: The substrate is titanium metal or titanium alloy.
3. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: In the first step, the fluorine-containing electrolytic solution includes 2-10 parts of ammonium chloride, 56-60 parts of propylene glycol, and 1-5 parts of potassium permanganate, calculated by mass.
4. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: In the first step, the voltage of the first anodization is 20-30V, and the time of anodization is 5-15 minutes.
5. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: In the first step, the voltage of the secondary anodization is 20-30V, and the anodization time is 5-15min.
6. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: In the second step, the voltage of the final anodization is 40-50V, and the anodization time is 20-30min.
7. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: In the third step, the preparation method of the alginate gel is as follows: sodium alginate powder is slowly added to deionized water while stirring until it is completely dissolved to obtain a solution with a concentration of 2%wt, dilute sodium hydroxide is used to adjust the pH value of the sodium alginate solution to 9 to promote the cross-linking reaction, and calcium ion solution is added dropwise to the sodium alginate solution, and the calcium ions immediately combine with the anionic groups on the alginate chain to form an alginate gel.
8. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: The heat treatment is carried out in an oxygen-containing atmosphere, the heat treatment temperature is 300-500° C., and the heat treatment time is 1.5-3 hours.
9. The composition containing titanium dioxide nanotubes according to claim 1, characterized in that: The pore diameter of the titanium dioxide nanotubes in the composition containing titanium dioxide nanotubes is 10-60 nm.
10. Use of a composition containing titanium dioxide nanotubes according to any one of claims 1 to 9 in preparing a product for promoting differentiation of mesenchymal stem cells, characterized in that: The composition containing titanium dioxide nanotubes is used for preparing a product for promoting the differentiation of mesenchymal stem cells.
